Aortic Valve Replacement for Moderate Aortic Stenosis with Severe Calcification and Left Ventricualr Dysfunction—A Case Report and Review of the Literature - Narang, Nikhil; Lang, Roberto M.; Liarski, Vladimir M.; Jeevanandam, Valluvan; Hofmann Bowman, Marion A. (Frontiers in Cardiovascular Medicine, 2017)
A 55 year-old male with a history of erosive, seropositive rheumatoid arthritis (RA) and interstitial lung disease (ILD) presented with shortness of breath. Echocardiography showed new onset severe left ventricular (LV) dysfunction with an ejection fraction (EF) of 15%, moderately increased mean aortic valve gradient of 20 mmHg in a tri-leaflet aortic valve with severe sclero-calcific degeneration. Coronary angiography revealed no significant obstructive coronary disease. Invasive hemodynamic studies and dobutamine stress echocardiography were consistent with moderate aortic stenosis. Guideline directed medical therapy for heart failure with reduced ejection fraction (HFrEF) was initiated, however diuretics and neurohormonal blockade (beta blocker and angiotensin receptor blocker) provided minimal improvement and the patient remained functionally limited. Of interest, echocardiography performed one year prior to his presentation showed normal LV EF and mild aortic leaflet calcification with moderate stenosis, suggesting a rapid progressing of calcific aortic valve disease. Subsequently, the patient underwent surgical aortic valve replacement (sAVR) and demonstrated excellent post-surgical recovery of LV EF (55%). Calcific aortic valve disease is commonly associated with aging, bicuspid aortic valve, and chronic kidney disease. Pathophysiological mechanism for valvular calcification are incompletely understood, but include osteogenic transformation of valvular interstitial cells mediated by local and systemic inflammatory processes. Several rheumatologic diseases including RA are associated with premature atherosclerosis and arterial calcification, and we speculated a similar role of RA accelerating calcific aortic valve disease. We present a case of accelerated aortic valve calcification with (only) moderate stenosis, complicated by a rapid decline in LV systolic performance. Guidelines for AVR in moderate stenosis without concomitant cardiac surgery are not well established, though it should be considered in selected patients.